Características psicométricas dos instrumentos usados para avaliar a qualidade de vida na esclerose múltipla: uma revisão bibliográfica - Pedro, Luisa (2008)
A esclerose múltipla (EM) é a doença crónica neurológica que mais afeta adultos jovens; em 80% dos casos, a doença progride para situações de níveis variados de incapacidade, o que torna necessário avaliar a qualidade de vida (QV) desses indivíduos. O objetivo desta revisão foi localizar estudos que avaliam a QV em indivíduos com EM, identificando os instrumentos utilizados e suas características psicométricas. Foram consultadas as bases Psycinfo, Psycarticles, Psycbooks, Psychology & Behavioral Science Collection, EJS E-Journal, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Medline, e Academic Search Complete, utilizando os descritores 'multiple sclerosis' e 'quality of life', para localizar artigos publicados no período 1997-2007. Foram selecionados 1.376 artigos e, após a leitura dos resumos, excluídos os referentes a instrumentos que não tinham boas características psicométricas e/ou eram pouco referenciados. Foram encontrados 461 artigos, dos quais 267 usaram instrumentos genéricos e 194 específicos para a EM. Dos 7 instrumentos (2 genéricos, 5 específicos) com boas características psicométricas utilizados pelos estudos consultados, o mais usado é o SF-36 (em 237 estudos). Todos os instrumentos têm validade verificada e apresentam grau elevado de confiabilidade, podendo ser utilizados para avaliação da qualidade de vida de pacientes com EM tanto em pesquisa quanto na clínica. ABSTRACT - Multiple sclerosis (MS) is the chronic neurological disease that most affects young adults; 80% of patients experience a transition towards persistent disability, hence the need to assess their quality of life (QoL). The aim of the study was to review studies that assess QoL in patients with multiple sclerosis, inquiring on the instruments used and their psychometric features. Articles published from 1997 through 2007 were searched for by means of key words 'multiple sclerosis' and 'quality of life' in databases Psycinfo, Psycarticles, Psycbooks, Psychology & Behavioral Science Collection, EJS E-Journal, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Medline, and Academic Search Complete. From the 1,376 studies found, after abstract reading those that reported on instruments with poor psychometric properties and/or were little referred were excluded. A total of 461 articles were selected, of which 267 reported using generic instruments and 194, MS-specific ones. Among the 7 instruments reported by the studies as having good psychometric characteristics (2 generic, five MS-specific), the most used is the SF-36 (by 237 studies). All instruments have shown adequate psychometric properties and a high degree of reliability, hence may be used to assess QoL in subjects with multiple sclerosis both in clinic and research.